Palmitate and group B Streptococcus synergistically and differentially induce IL-1β from human gestational membranes - Gaddy, Jennifer A.; Moore, Rebecca E.; Lochner, Jonathan S.; Rogers, Lisa M.; Noble, Kristen N.; Giri, Ayush; Aronoff, David M.; Cliffel, David; Eastman, Alison J. (Frontiers in Immunology, 2024)
Rupture of the gestational membranes often precedes major pregnancy complications, including preterm labor and preterm birth. One major cause of inflammation in the gestational membranes, chorioamnionitis (CAM) is often a result of bacterial infection. The commensal bacterium Streptococcus agalactiae, or Group B Streptococcus (GBS) is a leading infectious cause of CAM. Obesity is increasing worldwide; roughly 1 in 4 pregnancy complications is related to obesity; individuals with obesity are also more likely to be colonized by GBS. The gestational membranes are comprised of several distinct cell layers which are, from outermost to innermost: maternally-derived decidual stromal cells (DSC), fetal cytotrophoblasts, fetal mesenchymal cells, and fetal amnion epithelial cells (AECs). In addition, the gestational membranes have several immune cell populations; macrophages are the most common phagocyte in the membranes. Here we characterize the effects of palmitate, the most common long-chain saturated fatty acid, on the inflammatory response of each layer of the gestational membranes when infected with GBS, using human cell lines and primary human tissue. Palmitate itself slightly but significantly augments GBS proliferation. Palmitate and GBS co-stimulation synergized to induce many inflammatory proteins and cytokines, particularly IL-1b and matrix metalloproteinase 9 from DSCs, cytotrophoblasts, and macrophages, but not from AECs. Many of these findings are recapitulated when treating cells with palmitate and TLR agonists, suggesting broad applicability of palmitate-pathogen synergy. Co-culture of macrophages with DSCs or cytotrophoblasts, upon co-stimulation with GBS and palmitate, resulted in increased inflammatory responses, contrary to previous work in the absence of palmitate. In whole gestational membrane biopsies, the amnion appeared to dampen immune responses from the choriodecidua to GBS and palmitate co-stimulation. Addition of the monounsaturated fatty acid oleate, the most abundant monounsaturated fatty acid in circulation, dampened the proinflammatory effect of palmitate. These studies reveal a complex interplay between the immunological response of the distinct layers of the gestational membrane to GBS infection and that such responses can be altered by exposure to long-chain saturated fatty acids. These data provide insight into how metabolic syndromes such as obesity might contribute to an increased risk for GBS disease during pregnancy.